Analysis of Financial Literacy, Financial Attitude, and Locus of Control on Financial Management Behavior - Fazrin, Rahmawati; Fathihani, Fathihani (Institute Of Advanced Knowledge and Science, 2024)
This study was conducted with the aim of determining the effect of Financial Literacy, Financial Attitudes and Locus of Control on Financial Management Behavior. The sampling technique used was purposive sampling, which is a technique for taking data sources by determining samples with certain considerations. The data used is primary data using a questionnaire distributed to 100 respondents, namely the millennial generation in the Jakarta area. The analysis method uses the Statistical Product and Services Solution (SPSS) application. The results of this study are that Financial Literacy has a positive and significant effect on the Financial Management Behavior of the Millennial Generation in the Jakarta area. Financial Attitudes do not affect the Financial Management Behavior of the Millennial Generation in the Jakarta area. Locus of Control has a positive and significant effect on the Financial Management Behavior of the Millennial Generation in the Jakarta area.